Peran Zakat terhadap Proses Perubahan Sosial melalui Pemberdayaan Masyarakat: Studi Narrative dan Bibliometrics - Salahuddin El Ayyubi; Ekawati Wahyuni; Pudji Muljono; Irfan Syauqi Beik (AL-MUZARA'AH, 2023)
This paper presents an analysis of the development of literature on community empowerment through zakat and its relation to social change. A total of 29 documents published between 2016 and 2023 were analyzed using a narrative review approach and bibliometric analysis with the assistance of the RStudio application. Concept mapping and visualization of publications were conducted to identify elements of knowledge, dynamics, relationships, and interactions among publications. The analysis results show that research during the 2016-2023 period generally focuses on the economic aspect of zakat in social change. However, further research is needed to cover other dimensions of social change, such as politics, culture, technology, and environment. Consequently, the study of the impact of zakat on social change needs to be expanded to provide a more comprehensive understanding of the role of zakat in promoting inclusive and sustainable social change within society.